A note on some equipment used for boundary layer measurements in flight. Part 1, the design and construction of a large multitube manometer for use in flight. Part 2, two fixed head type combs for boundary layer investigations - Burrows, F. M. (College of Aeronautics, 1956)
Some notes are presented relating to the design and construction of a large multitube manometer and to two 'fixed head' type boundary layer combs to be used for the measurement in flight of the boundary layer characteristics of a swept back wing. Although the equipment described was designed with a particular object in view, there is no reason why the designs should not be modified as and where necessary for the construction of similar equipment.